2020
DOI: 10.3390/jcm9072227
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Presentation of Children Hospitalized with SARS-CoV-2 Infection in Suburbs of Paris

Abstract: Understanding the clinical presentation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and prognosis in children is a major issue. Children often present mild symptoms, and some severe forms require paediatric intensive care, with in some cases a fatal prognosis. Our aim was to identify the epidemiological characteristics, clinical presentation, and prognosis of children with coronavirus disease 2019 (Covid-19) hospitalized in Paris suburb hospitals. In this prospective, observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…A total of 18 studies reported prevalence of smell and/or taste dysfunction, most of them reported more than one type of prevalence among children with COVID-19. Specifically, 11 of the included studies reported the prevalence on smell dysfunction ( 13 , 25 , 27 , 28 , 30 , 34 36 , 40 ), 9 of the included studies reported prevalence on taste dysfunction ( 13 , 27 , 28 , 32 , 34 , 37 , 38 , 40 ), 10 of the included studies reported prevalence on smell or taste dysfunction ( 13 , 14 , 25 , 26 , 28 , 29 , 31 , 33 , 36 , 39 ), and 2 of the included studies reported prevalence on smell and taste dysfunction ( 13 , 28 ). Thus, four different types of prevalence were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies reported prevalence of smell and/or taste dysfunction, most of them reported more than one type of prevalence among children with COVID-19. Specifically, 11 of the included studies reported the prevalence on smell dysfunction ( 13 , 25 , 27 , 28 , 30 , 34 36 , 40 ), 9 of the included studies reported prevalence on taste dysfunction ( 13 , 27 , 28 , 32 , 34 , 37 , 38 , 40 ), 10 of the included studies reported prevalence on smell or taste dysfunction ( 13 , 14 , 25 , 26 , 28 , 29 , 31 , 33 , 36 , 39 ), and 2 of the included studies reported prevalence on smell and taste dysfunction ( 13 , 28 ). Thus, four different types of prevalence were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…For patients recruited in CHI Créteil disposable sterile swabs (Zhejiang Gongdong Medical Technology, China), and Vacuette Virus Transport Tubes (Greiner Bio-One, Austria) were used to collect the naso-pharyngeal samples. The COVID-19 RT-PCR test used was the Allplex 2019-nCoV kit (Seegene, South Korea) which targets two SARS-CoV-2-specific genes (RdRP and N gene) and one Sarbecovirus specific gene from the viral envelope (17).…”
Section: Sars-cov-2 Rt-pcr Methodsmentioning
confidence: 99%
“…Consistent with prior reports, we found greater proportions of younger children among hospitalized patients. 26 , 27 Laboratory tests obtained on hospital admission indicated abnormalities in inflammation and coagulation. Examination of management patterns revealed that the use of candidate therapeutic agents adopted in adult populations remained low in children and youth.…”
Section: Discussionmentioning
confidence: 99%
“…National-level data were not available for Singapore and only available for a 2-month period for the US. Additional visualizations, including interactive figures with cumulative counts by country are available online 25.…”
mentioning
confidence: 99%